2008
DOI: 10.1371/journal.pmed.0050135
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Brief Video Intervention on Incident Infection among Patients Attending Sexually Transmitted Disease Clinics

Abstract: BackgroundSexually transmitted disease (STD) prevention remains a public health priority. Simple, practical interventions to reduce STD incidence that can be easily and inexpensively administered in high-volume clinical settings are needed. We evaluated whether a brief video, which contained STD prevention messages targeted to all patients in the waiting room, reduced acquisition of new infections after that clinic visit.Methods and FindingsIn a controlled trial among patients attending three publicly funded S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(134 citation statements)
references
References 28 publications
5
129
0
Order By: Relevance
“…The reasons for each decision are given in Appendix 3. Articles were excluded for not being a RCT or other suitable study, as specified in our inclusion criteria; not having the sufficient percentage of MSM in the study population; [137][138][139][140][141][142][143][144][145] not including a sufficient percentage of HIV-negative participants; [146][147][148][149][150][151][152][153][154][155][156] or not being an individually focused intervention, instead focusing on groups or structural factors. [157][158][159][160][161][162][163][164][165][166][167] Other reasons for exclusion, such as interventions not being brief, reporting a pilot trial, reporting non-HIV-specific data (e.g.…”
Section: -106mentioning
confidence: 99%
“…The reasons for each decision are given in Appendix 3. Articles were excluded for not being a RCT or other suitable study, as specified in our inclusion criteria; not having the sufficient percentage of MSM in the study population; [137][138][139][140][141][142][143][144][145] not including a sufficient percentage of HIV-negative participants; [146][147][148][149][150][151][152][153][154][155][156] or not being an individually focused intervention, instead focusing on groups or structural factors. [157][158][159][160][161][162][163][164][165][166][167] Other reasons for exclusion, such as interventions not being brief, reporting a pilot trial, reporting non-HIV-specific data (e.g.…”
Section: -106mentioning
confidence: 99%
“…Video interventions, although limited due to a lack in interactivity, do offer the benefit of ease of implementation. [39][40][41] Computer technology may overcome some of the limits of video interventions due to its interactive nature; one computerized intervention for STI clinic patients was designed to customized the material provided based on a patient's baseline sexual risk and willingness to change behavior. This program resulted in an increased proportion of subjects reporting consistent condom use at 6 months and decreased proportion with recurrent STIs.…”
Section: Std Clinic Patientsmentioning
confidence: 99%
“…Safe in the City (Warner et al 2008) is an evidencebased video intervention shown in the waiting rooms of STD clinics. The 23 min video uses professional actors, art direction, cartoon graphics, and a witty theory-based pretested script to keep patients engaged and entertained while they wait for STD diagnostic and treatment services.…”
Section: Implementing Evidence-based Prevention Programs Based On Commentioning
confidence: 99%